The Impact of Using Social Media on Improving Fundraising Strategies: A Case Study of Non-Profit Organizations in Saudi Arabia (The International Journal of Educational Sciences and Arts, 2025)
The study aims to identify the impact of using social media in improving fundraising strategies, applying it to non-profit organizations in Saudi Arabia. The study is a descriptive study, based on a media survey methodology. The study sample consists of (400) individuals from the Saudi public who use non-profit association accounts on social media. A questionnaire was used as a data collection tool.The study reached a number of results, the most important of which are:-       The motive (to learn about the activities of non-profit associations in the Kingdom) came first among the study sample respondents' motives for using the accounts of non-profit associations in the Kingdom of Saudi Arabia on social media sites, with an arithmetic mean of (2.88). In second place came the motive (because I am interested in the field of non-profit associations) with an average of (2.86), followed by the motive (to learn about the Kingdom's efforts in supporting the non-profit sector) in third place with an average of (2.79).-       The study sample respondents believe that the feature of (continuous account updating) comes at the forefront of the features of non-profit associations’ accounts in the Kingdom on social media sites from their point of view, with an arithmetic mean of (2.87). In second place came the feature of (continuous communication with the public) with an average of (2.82), followed by the feature of (displaying the associations’ activities supported by multimedia) in third place with an average of (2.80).-       The phrase "social media has helped in spreading the word to various associations in the Kingdom" came at the forefront of respondents' trends regarding the use of social media by non-profit associations in the Kingdom, with an average of (2.89). In second place came the phrase "utilizing social media in a good way helps in increasing donations" with an arithmetic average of (2.85).
Keywords: Social media; strategies; donations; non-profit organizations; Saudi Arabia